2018
DOI: 10.3389/fpsyg.2018.00552
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Party Ideology Among Politicians. A Closer Look at Political Elites From Canada and Belgium

Abstract: We examined the relationship between Big Five personality and the political ideology of elected politicians. To this end, we studied 303 politicians from Flanders, Wallonia, and Canada, relating their self-reported Big Five scores to a partisanship-based measure of political ideology. Our findings show that, in line with the congruency model of personality, Openness to Experience is the best and most consistent correlate of political ideology, with politicians high on Openness to Experience being more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…US Republican legislators scored higher on Conscientiousness (Dietrich et al, 2012;Hanania, 2017), but lower on Openness and Agreeableness than Democratic legislators. Joly et al (2018) report that left-wing Canadian and Belgian politicians scored higher on Openness than right-wing politicians. With regard to Honesty-Humility, no previous study has investigated the link between political ideology and self-reported levels of politicians.…”
Section: Ideological Differences Between Politiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…US Republican legislators scored higher on Conscientiousness (Dietrich et al, 2012;Hanania, 2017), but lower on Openness and Agreeableness than Democratic legislators. Joly et al (2018) report that left-wing Canadian and Belgian politicians scored higher on Openness than right-wing politicians. With regard to Honesty-Humility, no previous study has investigated the link between political ideology and self-reported levels of politicians.…”
Section: Ideological Differences Between Politiciansmentioning
confidence: 99%
“…Several recent studies provide information about personality trait levels of politicians in the Big Five or Five-Factor model (FFM) framework using questionnaire-based data (Best, 2011;Caprara, Barbaranelli, Consiglio, Picconi, & Zimbardo, 2003;Dietrich, Lasley, Mondak, Remmel, & Turner, 2012;Hanania, 2017;Joly, Hofmans, & Loewen, 2018;Nørgaard & Klemmensen, 2018;Vecchione, Castro, & Caprara, 2011) or speech analysis (Ramey, Klingler, & Hollibaugh, 2016). These studies have mapped personality differences between politicians and citizens, as well as differences between politicians.…”
Section: Introductionmentioning
confidence: 99%
“…Caprara et al (2003) showed that center-right Italian politicians were higher in extraversion and conscientiousness than center-left politicians. In Canada, politicians' extraversion was correlated with left orientation (Joly, Hofmans & Loewen, 2018). In a Belgian sample, conscientiousness (positively) and agreeableness (negatively) were correlated with a center-right preference (Van Hiel et al, 2004).…”
Section: Political Preferences and Personalitymentioning
confidence: 89%
“…Most of the texts published on this topic are about political orientation and voter decision-making; active politicians are only seldom considered. Italy has done some research based on samples of politicians (Caprara, Barbarenelli, Consiglio, Picconi & Zimbardo, 2003), so has Belgium (Joly, Hofmans & Loewen, 2018). Yet, there is a lack of published research on the relevant parties within the large multi-party transitioning political systems of former communist countries.…”
Section: Introductionmentioning
confidence: 99%
“…Do these differences between liberals and conservatives emerge because of personality differences between these politicians? Survey research shows that Conservative MPs score higher on conscientious and lower on openness to experience than liberal or left-wing MPs [58][59][60]. These personality traits are associated with preferences for linguistic complexity.…”
Section: Resultsmentioning
confidence: 99%